A conserved role of αA-crystallin in the development of the zebrafish embryonic lens. (September 2015) - Zou, Ping; Wu, Shu-Yu; Koteiche, Hanane A.; Mishra, Sanjay; Levic, Daniel S.; Knapik, Ela; Chen, Wenbiao; Mchaourab, Hassane S.
Abstract: αA- and αB-crystallins are small heat shock proteins that bind thermodynamically destabilized proteins thereby inhibiting their aggregation. Highly expressed in the mammalian lens, the α-crystallins have been postulated to play a critical role in the maintenance of lens optical properties by sequestering age-damaged proteins prone to aggregation as well as through a multitude of roles in lens epithelial cells. Here, we have examined the role of α-crystallins in the development of the vertebrate zebrafish lens. For this purpose, we have carried out morpholino-mediated knockdown of αA-, αBa- and αBb-crystallin and characterized the gross morphology of the lens. We observed lens abnormalities, including increased reflectance intensity, as a consequence of the interference with expression of these proteins. These abnormalities were less frequent in transgenic zebrafish embryos expressing rat αA-crystallin suggesting a specific role of α-crystallins in embryonic lens development. To extend and confirm these findings, we generated an αA-crystallin knockout zebrafish line. A more consistent and severe lens phenotype was evident in maternal/zygotic αA-crystallin mutants compared to those observed by morpholino knockdown. The penetrance of the lens phenotype was reduced by transgenic expression of rat αA-crystallin and its severity was attenuated by maternal αA-crystallin expression. These findings demonstrate that the role of α-crystallins in lens development is conserved from mammals to zebrafish and set the stage for using the embryonic lens as a model system to test mechanistic aspects of α-crystallin chaperone activity and to develop strategies to fine-tune protein–protein interactions in aging and cataracts. Highlights: We generated and characterized the first zebrafish knockout mutant for αA-crystallin. Loss of αA-crystallin severely affects zebrafish embryonic lens morphology. Maternal expression of αA-crystallin plays a role in early zebrafish lens development. The role of αA-crystallin in lens development is conserved in vertebrates. Our results demonstrate a relevant usage of zebrafish lens to study α-crystallin functions in vivo .